COMPARISON OF THE PHYSICAL FITNESS OF WATER RESCUE GUARDS FROM RURAL AND URBAN AREAS (Physical Culture and Sport: Scientific Perspective, 2024)
The work is of a research nature. The aim was to determine the level of physical development and motor skills of students aged 10-11 from two different environments: rural and urban. Physical development was determined based on height and weight. The Rohrer index was calculated and the Kretschmer typological system was used. The International Physical Fitness Test was used to assess the level of physical fitness. The test results indicate that women from rural areas showed a higher level of fitness tests than girls from the city. However, in the case of boys, the tests showed a similar level of fitness. After calculating the results, all groups were in the average physical fitness range. However, the points obtained allowed the conclusion that both women and men from rural areas have better physical fitness than their peers from the city. The purpose of the fitness test is to objectively assess the development of motor skills, general performance and physical fitness as well as technical skills. Such tests can be used individually and in groups. They can be performed at any age. The tests were developed mainly for rescuers aged 18-25, because most rescuers work in this age group.
Keywords: physical development; physical fitness; urban environment; rural environment; motor skills; rescuer